Ethic and Economic Aspects of the Value and its Adaptation in to the Eating out Industry - Gudačiauskas, Darius (Ekonomika, 1999)
The main issue pursued in my article is how to strengthen competitiveness of the Lithuanian eating-out industry in an increasingly competitive business environment, which would increase attractiveness of Lithuania to foreign investors, tourists and guests. The analysis of eating-out industry enabled me to identify one of the most problematic business development sides - service value. On the basis of industry analysis and ethical value aspect analysis I have formulated value strategy that could be implemented in eating-out companies. Successful implementation of this strategy in to the Lithuanian market is the key to business growth that would build extra job places and would be a considerable support to overall government strategy of enchancing the country’s economic activity and social welfare.